الرقابة القضائية على أعمال المجلس الشعبي البلدي - أحمد التجاني, سليماني (جامعة الوادي.University eloued, 2021)
"الرقابة القضائية هي الرقابة التي تمارسها هيئة قضائية تختص بالفصل في القرارات أي والقوانين التي تصدرها الإدارة المحلية، وينطلق مفهوم الرقابة القضائية على الإدارة من فكرة حق الأفراد في حماية حقوقهم وحرياتهم المقررة بموجب القوانين والدساتير، فوظيفة القضاء تتمثل في الفصل في الخصومات التي تحصل بين الأفراد والدولة أو بين الأفراد أنفسهم وهي وظيفة على قدر كبير من الأهمية، كما تشكل الرقابة القضائية ضمانة فاعلة لتطبيق القوانين حيث يتسم القضاء بالحياد والنزاهة والاستقلالية بالإضافة إلى الخبرة القانونية. لقد منح المشرع الجزائري للمجالس المنتخبة المحلية صلاحيات واسعة في اتخاذ القرارات الإدارية، تتمثل هذه القرارات في أعمال إدارية صادرة من سلطة مختصة بقصد إحداث أثر قانوني إما تعديل أو إلغاء، وإما أن تكون قرارات رئيس المجلس الشعبي البلدي مخاطبة للفرد أو الجماعة، مثلا له سلطة إصدار قرارات في الشأن المحلي وقرارات في مجال الضبطية، لكن بطبيعة الحال هذه القرارات تكون عن طريق مداولات المجلس الشعبي البلدي ومن ثم يصدرها رئيس. إن قرارات رئيس المجلس الشعبي البلدي لا تسلم من نقد والطعن فيها وبالتالي تكون هذه القرارات معرضة للإلغاء عن طريق دعوى الإلغاء وطعن فيها أمام الجهات المختصة. ومنه نستنتج أن صلاحيات رؤساء المجالس المنتخبة المحلية والمجالس المنتخبة المحلية تبقى مقيدة عن طريق الرقابة، إما تكون رقابة وصاية عن طريق الوالي وهي رقابة لاحقة وإما أن تكون رقابة قضائية عن طريق رفع دعوى لإلغاء قرارات رئيس المجلس الشعبي البلدي. " Judicial oversight is the oversight exercised by a judicial body competent to adjudicate decisions, that is, laws issued by the local administration. The concept of judicial oversight over administration stems from the idea of individuals’ right to protect their rights and freedoms established by laws and constitutions. The function of the judiciary is to adjudicate disputes that occur between individuals and the state. Or between individuals themselves, which is a very important function, and judicial oversight is an effective guarantee for the application of laws, where the judiciary is impartial, impartial and independent, in addition to legal expertise. The Algerian legislator has granted the local elected councils wide powers to make administrative decisions. These decisions are administrative actions issued by a competent authority with the intent of creating a legal effect either to amend or cancel, or for the decisions of the President of the Municipal People’s Assembly to address the individual or the group, for example he has the power to issue Decisions in the local matter and decisions in the field of seizure, but of course these decisions are made through the deliberations of the Municipal People's Council and then issued by the President. The decisions of the President of the Municipal People's Council are not free from criticism and appeal, and therefore these decisions are subject to cancellation through a rescission lawsuit and appealed before the competent authorities. From this, we conclude that the powers of the heads of local elected councils and local elected councils remain restricted through supervision, either it is guardianship control through the governor, which is a subsequent control, or it is judicial control by filing a lawsuit to cancel the decisions of the president of the Municipal People’s Council.
ماسترقانون إداري
Keywords: الرقابة - القضاء; Censorship - Judiciary